Innate immune responses and antioxidant/oxidant imbalance are major determinants of human Chagas disease. - Dhiman, Monisha (2013)
We investigated the pathological and diagnostic role of selected markers of inflammation, oxidant/antioxidant status, and cellular injury in human Chagas disease. METHODS: Seropositive/chagasic subjects characterized as clinically-symptomatic or clinically-asymptomatic (n = 116), seronegative/cardiac subjects (n = 102), and seronegative/healthy subjects (n = 45) were analyzed for peripheral blood biomarkers. RESULTS: Seropositive/chagasic subjects exhibited an increase in sera or plasma levels of myeloperoxidase (MPO, 2.8-fold), advanced oxidation protein products (AOPP, 56%), nitrite (5.7-fold), lipid peroxides (LPO, 12-17-fold) and malondialdehyde (MDA, 4-6-fold); and a decline in superoxide dismutase (SOD, 52%) and glutathione (GSH, 75%) contents. Correlation analysis identified a significant (p<0.001) linear relationship between inflammatory markers (AOPP/nitrite: r = 0.877), inflammation and antioxidant/oxidant status (AOPP/glutathione peroxidase (GPX): r = 0.902, AOPP/GSH: r = 0.806, Nitrite/GPX: 0.773, Nitrite/LPO: 0.805, MDA/MPO: 0.718), and antioxidant/oxidant levels (GPX/MDA: r = 0.768) in chagasic subjects. Of these, MPO, LPO and nitrite biomarkers were highly specific and sensitive for distinguishing seropositive/chagasic subjects from seronegative/healthy controls (p<0.001, training and fitting AUC/ROC >0.95). The MPO (r = 0.664) and LPO (r = 0.841) levels were also correlated with clinical disease state in chagasic subjects (p<0.001). Seronegative/cardiac subjects exhibited up to 77% decline in SOD, 3-5-fold increase in LPO and glutamate pyruvate transaminase (GPT) levels, and statistically insignificant change in MPO, AOPP, MDA, GPX, GSH, and creatine kinase (CK) levels. CONCLUSIONS: The interlinked effects of innate immune responses and antioxidant/oxidant imbalance are major determinants of human Chagas disease. The MPO, LPO and nitrite are excellent biomarkers for diagnosing seropositive/chagasic subjects, and MPO and LPO levels have potential utility in identifying clinical severity of Chagas disease